PENGARUH EMPLOYER BRANDING DALAM MEMBANGKITKAN INTENTION TO APPLY DENGAN MEDIASI CORPORATE REPUTATION, SOCIAL MEDIA USAGE, DAN ONLINE REVIEWS - Jeremiah, Dearyl; Nurlaela, Siti (JURNAL LENTERA BISNIS, 2026)
Competition among companies in recruiting employees has intensified in the digital era, encouraging organizations to implement employer branding strategies to attract younger generations who are increasingly selective in choosing workplaces. This study aims to examine the influence of employer branding, corporate social responsibility (CSR), healthy work atmosphere, compensation and benefits, work-life balance, and training and development on intention to apply, with corporate reputation, social media usage, and online reviews as mediating variables. The population consists of final-year undergraduate students in the Greater Jakarta area (Jabodetabek), selected using purposive sampling, with 233 respondents participating in a quantitative survey. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that employer branding, CSR, healthy work atmosphere, and training and development positively affect intention to apply, while compensation and benefits and work-life balance have no significant effect. Corporate reputation and social media usage mediate the relationship between employer branding and intention to apply, whereas online reviews do not. These findings provide managerial implications for designing effective employer branding strategies to attract final-year students and fresh graduates.